In situ crosslinked dialdehyde guar gum-chitosan Schiff-base hydrogels for dual drug release in colorectal cancer therapy. (5th April 2023) - Dalei, Ganeswar; Das, Subhraseema; Ranjan Jena, Soumya; Jena, Debasis; Nayak, Jasmine; Samanta, Luna
Graphical abstract: Highlights: In situ crosslinked chitosan-dialdehyde guar gum Schiff-base hydrogels synthesized. Dialdehyde guar gum was accomplished by periodate oxidation of guar gum. Curcumin and aspirin dual drug release from hydrogels was optimum in colorectal pH. Combined formulation showed enhanced anticancer effects in HT-29 colon cancer cells. Hydrogels were potent for simultaneous chemotherapy and pain relief in CRC therapy. Abstract: This work advocates that in situ crosslinked chitosan-dialdehyde guar gum (CsDAGG) hydrogels can be effectually used for dual drug release in colorectal cancer therapy. Herein, we designed various grades of CsDAGG hydrogels where DAGG was accomplished by periodate oxidation of guar gum. With increasing DAGG content, a diminution in swelling and a more compact matrix was evident. In this study, curcumin in combination with aspirin were chosen for investigation in colon carcinoma. The hydrogels ensured the protection of the drugs from absorption in stomach and small intestine and enabled a controlled release at the targeted site of colorectum. The exposure of the aforesaid combined drug formulation further demonstrated enhanced anticancer effects in HT-29 colon cancer cells. The findings altogether suggested the high potency of the developed hydrogels for the co-administration of drugs that can provide chemotherapy and pain relief simultaneously in colorectal cancer combination therapy.